2009
DOI: 10.1007/s12177-009-9016-8
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure profile during the modified diurnal tension curve using Goldman applanation tonometry and dynamic contour tonometry

Abstract: The aim of this study was to compare the intraocular pressure (IOP) profile during the modified diurnal tension curve (mDTC) using Goldman applanation tonometry (GAT) and dynamic contour tonometry (DCT) in treated glaucomatous eyes. Eligible subjects were submitted to the mDTC using GAT and DCT in this sequence. IOP measurements were performed at 8 a.m., 10 a.m., 2 p.m., and 4 p.m.. Central corneal thickness was measured using ultrasound pachymetry in the morning. Statistical analysis was performed using paire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Mean deviation was recorded as an objective parameter. Only reliable MD values were used, excluding examinations with 20% fixation errors and <33% false- positives or false-negatives 19 , 25 , 29 . Study eyes from the NTG group were graded into groups according to the visual field impairment: mild (MD > −6 dB), moderate (MD between −6 and −12 dB and severe (MD < −12 dB) glaucomatous damage 30 .…”
Section: Methodsmentioning
confidence: 99%
“…Mean deviation was recorded as an objective parameter. Only reliable MD values were used, excluding examinations with 20% fixation errors and <33% false- positives or false-negatives 19 , 25 , 29 . Study eyes from the NTG group were graded into groups according to the visual field impairment: mild (MD > −6 dB), moderate (MD between −6 and −12 dB and severe (MD < −12 dB) glaucomatous damage 30 .…”
Section: Methodsmentioning
confidence: 99%
“…[189][190][191][192] three in each of Saudi Arabia, [193][194][195] India, [196][197][198] Portugal 106,199,200 and Greece [201][202][203] and two in Taiwan, 125,204 Israel, 205,206 the Netherlands, 207,208 Sweden 209,210 and Turkey. 211,212 One study took place in each of Austria, 126 Brazil, 213 France, 123 Ireland, 214 New Zealand, 215 Norway 216 and Denmark. 217 One additional study was reported as a multicentre study, taking place in Italy and Spain.…”
Section: Overviewmentioning
confidence: 99%